Malaysia–Global Industrial Linkages: lifelong learning lessons from Xi’an Muslim Street - Jamal, Siti Norazura; Zulkifliz, Nordayana; Mohamad, Masilah; Mohd Aris, Aslizah; Ibrahim, Muhammad Aidil (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Malaysia is committed to strengthening global industrial linkages through collaborations, industry visits, and cultural exchanges. The recent Malaysia–Global Industrial Linkages trip to Xi’an, China, transformed from a formal mission into a valuable lifelong learning experience. Similar to the AURORA Collective Team (Alliance for Unified Research in Organization, Regulation, and Applied Biosciences) delegation from UiTM Negeri Sembilan, they also view Xi’an’s Muslim Street as a living classroom and a platform to learn valuable lessons. The street reveals lessons in history, culture, and entrepreneurship, showing that learning continues beyond formal education.